Local extension staging of sinonasal tumours: retrospective comparison between CT/MRI assessment and pathological findings. (25th January 2017) - Mortuaire, G.; Camous, D.; Vandenhende‐Szymanski, C.; Dubrulle, F.; Chevalier, D.
Abstract : Objectives: To assess the reliability of clinical staging with CT and MRI in sinonasal cancers. Methods: We conducted a retrospective review of patients who underwent surgery for a sinonasal cancer. The 7th edition of the TNM classification was used to establish tumour staging. Standardised preoperative CT/MRI staging was compared with the pathological staging based on specimens obtained during surgery from each subsite within and around the tumour. Results: We analysed data from 68 patients between January 2010 and December 2014. A comparison of cT and pT stages was established for 49 naso‐ethmoidal and 16 maxillary tumours. Clinical staging for naso‐ethmoidal cT1 and maxillary cT2 was consistent with pathological results. Clinical staging for naso‐ethmoidal cT2, cT3 and cT4b was overstated in comparison with pT findings. The positive predictive value of imaging was <65% for the lamina papyracea, the cribriform plate, the dura, and the frontal and sphenoid sinuses. Sensitivity was over 75% for each anatomical site except for the cribriform plate (73.3%) and the sphenoid sinus (57.2%). Conclusion: Systematic pathologic analysis of the anatomical areas around the sinonasal cancer has to be applied in further studies to improve our therapeutic management. CT/MRI mapping cannot replace accurate assessment of tumour extension during surgery.